2000
DOI: 10.1192/pb.24.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric trainees' experiences of, and reactions to, patient suicide

Abstract: Aims and MethodThis survey is the first UK study of trainee psychiatrists' experiences of patient suicide. One hundred and three senior and specialist registrars in psychiatry working in Scotland completed the questionnaire, representing an 81% response rate.ResultsAlmost half (47%) had experienced suicide of a patient in their care or otherwise known to them (e.g. through on-call experiences). Although only 28% recalled previous training on issues to consider following a suicide, all of these doctors found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 11 publications
6
80
4
1
Order By: Relevance
“…6 Greater emphasis on dealing with patient suicide during psychiatric training has been previously highlighted as a potential way to reduce the distressing effect on psychiatrists. In Dewar et al's study, 12 those who had received such training found it helpful in the long run. Chemtob et al 5 and Hendin et al 8 both identified trainee psychiatrists and those with less experience to be at greater risk of distress after a patient dies by suicide, and thus highlight the need for training; in one study only a third of psychiatric residents had received any instruction in this area.…”
Section: Discussionmentioning
confidence: 99%
“…6 Greater emphasis on dealing with patient suicide during psychiatric training has been previously highlighted as a potential way to reduce the distressing effect on psychiatrists. In Dewar et al's study, 12 those who had received such training found it helpful in the long run. Chemtob et al 5 and Hendin et al 8 both identified trainee psychiatrists and those with less experience to be at greater risk of distress after a patient dies by suicide, and thus highlight the need for training; in one study only a third of psychiatric residents had received any instruction in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Courtenay & Stephens (2001) found that 51% of their psychiatric trainees reported a moderate emotional impact after a patient suicide and 24% reported a severe emotional impact. Chemtob et al (1988), Gitlin (1999), Alexander et al (2000), Dewar et al (2000), Courtenay & Stephens (2001), Yousaf et al (2002) Dewar et al (2000) likewise reported significant effects on psychiatric trainees following patient suicide: 31% reported an adverse effect on their personal lives and 39% an adverse effect on their work. In addition, 9% considered a change of career in the aftermath of patient suicide.…”
Section: Effects On Mental Health Workersmentioning
confidence: 97%
“…Dewar et al (2000) approached 128 trainee psy chiatrists in Scotland, 47% of the 103 respondents reported the suicide of a patient who was under their care; the number of suicides experienced ranged from one to five. In addition to the 47% who reported direct experience of patient suicide, a further 40% had been involved in the consequences of suicide (e.g.…”
Section: Incidencementioning
confidence: 99%
“…The largest survey was conducted in Scotland (Alexander 2000;Dewar 2000). In the context of this article, in terms of their personal response to events, it is noteworthy that 15 of the 31 consultants who had attended a fatal accident inquiry reported this to have been either 'unhelpful' (for 8) or 'very unhelpful' (for 7).…”
Section: Coping With Suicidementioning
confidence: 99%
“…In essence, it is important to appreciate that it is usual for psychiatric professionals to experience emotional trauma following the suicide of a patient, and to expect that support will be required by everyone involved, irrespective of their level of seniority (Alexander 2000;Dewar 2000;Courtenay 2001;Ruskin 2004). All of these papers give useful insights and advice relevant to psychiatrists in coping with the emotional aftermath of a patient's suicide, and in this area the paper by Campbell & Fahy (2002) may be found to be especially helpful.…”
Section: Coping With Suicidementioning
confidence: 99%